Síntese, caracterização e aplicação de um compósito de quitosana e HDL (Mg/Al/CO3) na adsorção de fosfato - Ribeiro, Nathália Isidoro (2021)
In the present work, the phosphate adsorption was studied using a composite formed by Layered Double Hydroxide (LDH) type Mg6Al2(CO3)(OH)16.4H2O and chitosan. For this, the composite was synthesized by the co-precipitation method of its constituents and applied in the phosphate adsorption, and its performance was compared to the adsorption performance of the same anion of chitosan and LDH individually. All adsorbents were characterized before and after adsorption tests by Scanning Electron Microscopy coupled with Energy Dispersive Spectroscopy (SEM-EDS), X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Adsorption of nitrogen (BET). According to the characterization, the adsorbents were successfully synthesized and their structure did not change after being used in phosphate adsorption. It suggests that the anion adsorption occurred by electrostatic interaction with the surface of the studied materials. According to the adsorption kinetic study, it was observed that the removal (57.2%, starting from the initial concentration of 63.3 mg/L, at 25°C±1) and the loading (120.8 mg/g) presented by the composite were greater than twice those presented by LDH (21.6% and 54.9 mg/g) and chitosan (20.7% and 45.2 mg/g) individually, under similar experimental conditions. The Pseudo-first Order, Pseudo-second Order, Elovich and Intraparticle Diffusion models were fitted to the data and the best fits were obtained by the Pseudo-second Order model for LDH (R2 = 0.98) and the composite LDH/Chitosan (R2 = 0.98) and PseudoFirst Order for chitosan (R2 = 0.96). For the equilibrium study, the Langmuir, Freundlich and Temkin models were used, with the Freundlich model being the one that best fit the experimental data (R2 = 0.98). These results show that there was an interaction between the constituents of the LDH/Chitosan composite that enhanced its phosphate adsorption capacity, allowing it to be effectively applied for this purpose. Keywords: hydrotalcite, phosphate removal, wastewater treatment.